1999
DOI: 10.1007/s004050050119
|View full text |Cite
|
Sign up to set email alerts
|

Expression of c-erb B-2 oncoprotein in cancer of the larynx in relation to invasion of the cartilagenous framework and prognosis

Abstract: Oncogenes are important cellular genes that in general promote in the normal growth regulatory pathways. The human c-erb B-2 proto-oncogene (HER-2 or neu) encodes a 185 kDa transmembrane putative growth factor receptor of the tyrosine kinase family. This oncogene has been shown to be over expressed and/or amplified in primary carcinoma of the breast, ovary, pancreas and salivary glands. This study was conducted to evaluate a possible link between amplification of c-erb B-2 oncoprotein and cartilage invasion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…While over-expression of p53 was significantly associated with the presence of lymph node metastases (P = 0.006), we failed to find any significant correlation between c-erbB-2 and lymph node status. This result is consistent with previous studies showing no correlation between lymph node status and c-erbB-2 positive immunostaining [7,19]. Our result is similar to the studies that reported higher p53 expression when lymph node metastases were present [2,15].…”
Section: Discussionsupporting
confidence: 96%
See 4 more Smart Citations
“…While over-expression of p53 was significantly associated with the presence of lymph node metastases (P = 0.006), we failed to find any significant correlation between c-erbB-2 and lymph node status. This result is consistent with previous studies showing no correlation between lymph node status and c-erbB-2 positive immunostaining [7,19]. Our result is similar to the studies that reported higher p53 expression when lymph node metastases were present [2,15].…”
Section: Discussionsupporting
confidence: 96%
“…The same findings were reported by other authors [2,7,13,19,21]. While over-expression of p53 was significantly associated with the presence of lymph node metastases (P = 0.006), we failed to find any significant correlation between c-erbB-2 and lymph node status.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations